2011
DOI: 10.1590/s0365-05962011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre questionários de qualidade de vida e sua correlação com a evolução clínica de pacientes com psoríase

Abstract: It was found that both clinical condition and quality of life improved in the majority of patients receiving care at this outpatient clinic and that the quality of life questionnaires are equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(12 reference statements)
0
5
0
4
Order By: Relevance
“…18 - 20 When psoriasis patients do continue with a prescribed course of treatment, HRQoL improves as long as clinical improvements are also shown. 21 One study of outpatients in Brazil with psoriasis found that decrements in HRQoL were due to physical symptoms and negative feelings causing heightened distress. 22 Another study with patients in Brazil distinguished psoriasis from other skin diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…18 - 20 When psoriasis patients do continue with a prescribed course of treatment, HRQoL improves as long as clinical improvements are also shown. 21 One study of outpatients in Brazil with psoriasis found that decrements in HRQoL were due to physical symptoms and negative feelings causing heightened distress. 22 Another study with patients in Brazil distinguished psoriasis from other skin diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Essas doenças podem estar presentes desde a infância e afetam a qualidade de vida do paciente ao interferir negativamente nos âmbitos físico, social e emocional de sua vida (Alvarenga & Caldeira, 2009;Barbarot et al, 2007;Gon, Gon, & Zazula, 2013;Manzoni et al, 2012;Silva, Fortes, Miot, & Marques, 2013;Tejada, Mendoza-Sassi, Almeida, Figueiredo, & Tejada, 2011;Torres, Silva, Magalhães, Morcillo, & Velho, 2011;Weber, Lorenzini, Reinehr, & Lovato, 2012). Rotina de tratamento, cuidados constantes com a pele, restrição na participação em atividades esportivas e de lazer e exposição a situações de estigmatização pela visibilidade das lesões podem dificultar a adaptação à doença e tornar-se um evento estressor recorrente (Castro & Piccinini, 2002;Gon, Rocha, & Gon, 2005;Pires & Cestari, 2005).…”
Section: Introductionunclassified
“…The disease is considered mild when indexes are ≤10 and moderate to severe when they are ≥10. 1 , 9 Patients assisted by the Dermatology Department of the State University of Campinas Medical School (FCM-UNICAMP), presenting mild to moderate psoriasis at the beginning of the protocol, participated in the research. The study selected individuals with a minimum age of 18 years, with no use of topical treatments or sudden changes of clinical presentation for at least two months.…”
mentioning
confidence: 99%